Legitimation in a World at Risk The Case of Genetically Modified Crops in India - Desmond, E.L (Springer Singapore, 2018)
This book provides a sociological analysis of the controversy surrounding genetically modified (GM) crops in the newly-formed state of Telangana, India. The issue of GM crops continues to be topical worldwide. There is much debate as to whether GM technology holds the key to improving the welfare of poor farmers globally or, instead, serves primarily to increase the profits of multinational corporations while enhancing cultivator risk. This is a particular concern for the impoverished agricultural contexts of the Global South whose plight continues to be used as a justification for extending the scope of the technology to more crops, locations and uses. Desmond's study is located in the economically vulnerable and politically volatile context of the Warangal district of Telangana. Warangal has been described as the most controversial district in India, not least given the strongly polarised views regarding the impact of GM crops on the high numbers of farmer suicides with which the district is associated. Uniquely foregrounding the perspectives of cultivators and the landless, Desmond explores how GM crops are variously legitimated and delegitimated in three Warangal villages by those whose livelihoods are at stake in the debate, but whose voices are rarely heard within it. This book will be significant for those with an interest in GM crops, power and knowledge and their relation to understandings of development, democracy and the global governance of risk. .